What evil means to us - Alford, Charles Fred (Cornell Univ. Press, 1997)
In interviewing working people, prisoners, and college students, the author discovered "a profound, inchoate feeling of dread so overwhelming that they tried to inflict it on others to be rid of it themselves. ... Our society suffers from a paucity of shared narratives and the creative imagination they inspire."--Jacket.
Keywords: Demônios; Deus; Goed en kwaad; Ontologia; Good and evil; Philosophie; Übel